Development and Validation of a Precise Method for Determination of Benzalkonium Chloride (BKC) Preservative, in Pharmaceutical Formulation of Latanoprost Eye Drops. Issue 1 (2010) - Mehta, J.; Patidar, K.; Vyas, N.
Abstract : A simple and precise reversed phase high performance liquid chromatographic method has been developed and validated for the quantification of benzalkonium chloride (BKC) preservative in pharmaceutical formulation of latanoprost eye drops. The analyte was chromatographed on a Waters Spherisorb CN, (4.6×250 mm) column packed with particles of 5 μm. The mobile phase, optimized through an experimental design, was a 40:60 (v/v) mixture of potassium dihydrogen orthophosphate buffer (pH 5.5) and acetonitrile, pumped at a flow rate of 1.0 mL/min at maintaining column temperature at 30 °C. Maximum UV detection was achieved at 210 nm. The method was validated in terms of linearity, repeatability, intermediate precision and method accuracy. The method was shown to be robust, resisting to small deliberate changes in pH, flow rate and composition (organic ratio) of the mobile phase. The method was successfully applied for the determination of BKC in a pharmaceutical formulation of latanoprost ophthalmic solution without any interference from common excipients and drug substance. All the validation parameters were within the acceptance range, concordant to ICH guidelines.